Fatigue damage development of grouted connection under varying cyclic loading. (October 2022) - Mantey, Selase Kwame; Zhang, Yi; Jiang, Jianqun; Amponsah, Evans; Wang, Zhenyu
Highlights: Axial fatigue test of grouted connection under variable load range and sequencing. Concrete damage plasticity-based model parameters used for numerical simulation. Damage accumulation rate increased after sudden high load. Load sequencing affects damage accumulation rate. The damage accumulation of the real sized model was similar to the experimental model. Abstract: The jacket structures of offshore wind turbines connect the foundation piles through a grout annulus. The grouted connections of the jacket structures are predominantly under the action of low-range fluctuating axial fatigue loads. However, they are sporadically subject to sudden large loads. The process of recurrent loading of the connection can lead to lose of capacity due to the gradual grout damage. Therefore, it is essential to study the damage accumulation process under variable fatigue loading. The cyclic compression tests of grouted connection scale model were performed and the influence of load-range, loading-sequence, and sudden large load on the fatigue damage accumulation was studied. The finite element models of experimental specimens and actual sized model were numerically simulated. An initial constant low load range yielded constant value of damage index and a sudden large load applied caused damage acceleration of the grout, which enhanced the development of damage under the subsequent low-range cyclic load. The larger load range prior to smaller load range created greater damage accumulation and reduced the residual vertical bearing capacity of the connection. The work offers a numerical basis for damage assessment of grouted connections of offshore wind turbines under variable axial fatigue load using the scalar damage degradation parameter in Abaqus finite element software.